KEPEMIMPINAN PEREMPUAN: Peran Ratu Ageng terhadap Perjuangan Pangeran Diponegoro dalam Perang Jawa 1825-1830 - Moh Ashif Fuadi (BUANA GENDER : Jurnal Studi Gender dan Anak, 2021)
The research aims to expose the issue of female leadership that is still being debated in islamic circles. In this research, the queen Ageng provides insight and firmness that the women are not subordinate by male's superiority in lifetime. Besides, the researchers used library research method. In this method, the researchers have several steps. The first, the researchers search for literature sources from a source to another source. The second, the researchers making a conclusion drawing and creating a new ideas. Furthermore, the result of this research is that queen Ageng as a female figure from Java that had a key role in the success of the 1825-1830 Java wars that inspired by prince Diponegoro. Moreover, the queen Ageng also has the role in character developing of prince Diponegoro.Â